2016
DOI: 10.3748/wjg.v22.i26.5896
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the role of molecular biomarkers as a potential weapon against gastric cancer: A review of the literature

Abstract: Gastric cancer (GC) is a global health problem and a major cause of cancer-related death with high recurrence rates ranging from 25% to 40% for GC patients staging II-IV. Unfortunately, while the majority of GC patients usually present with advanced tumor stage; there is still limited evidence-based therapeutic options. Current approach to GC management consists mainly of; endoscopy followed by, gastrectomy and chemotherapy or chemo-radiotherapy. Recent studies in GC have confirmed that it is a heterogeneous d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 124 publications
0
14
0
2
Order By: Relevance
“…Recently, multiple molecular biomarkers have been explored and reported to have potential efficacy as diagnostic and prognostic tools in gastric cancer. However, their use is still limited, and they need further validation to be used as markers of gastric cancer . The production of autoantibodies reflects greater immunologic reactivity in patients with cancer and enhanced immune surveillance for cancer cells .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, multiple molecular biomarkers have been explored and reported to have potential efficacy as diagnostic and prognostic tools in gastric cancer. However, their use is still limited, and they need further validation to be used as markers of gastric cancer . The production of autoantibodies reflects greater immunologic reactivity in patients with cancer and enhanced immune surveillance for cancer cells .…”
Section: Discussionmentioning
confidence: 99%
“…However, their use is still limited, and they need further validation to be used as markers of gastric cancer. (37) The production of autoantibodies reflects greater immunologic reactivity in patients with cancer and enhanced immune surveillance for cancer cells. (38) Autoantibodies to TAAs have recently received attention as potential biomarkers of cancer because they can be easily measured in serum obtained with minimally invasive blood sampling.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there have been some potential biomarkers that have emerged for the clinical diagnosis of GC, such as p27, cyclin E, E-cadherin, HER2, c-myc and p53. However, results have shown that there are no biomarkers that have been identified up-to-date that can be independently used for the occurrence and development of GC ( 6 ). Thus, developing molecular tag-based, sensitive and specific biomarkers for GC can have an important significance on the early diagnosis rate, effective treatment and reduced mortality of patients with GC.…”
Section: Introductionmentioning
confidence: 99%
“…These classification systems are useful for characterizing the cancer malignancy for each patient, but have little significance for determining the treatment plan and prognosis. Several treatment strategies for gastric cancer are currently in use, including chemotherapy, molecular targeting treatment, and immunotherapy; however, more precise molecular classification and determination of clinical markers in gastric cancer are required to improve treatment effectiveness . In 2014 The Cancer Genome Atlas (TCGA) Research Network classified gastric adenocarcinoma into four molecular subtype groups based on genomic database analysis: (i) Epstein–Barr virus‐associated DNA hypermethylation, (ii) microsatellite instability (MSI) high status, (iii) genomically stable (GS), and (iv) chromosomal instability (CIN) .…”
Section: Introductionmentioning
confidence: 99%